Integrated care model for patients with functional somatic symptom disorder - a co-produced stakeholder exploration with recommendations for best practice - Frank Röhricht; Carole Green; Maria Filippidou; Simon Lowe; Nicki Power; Sara Rassool; Katherine Rothman; Meera Shah; Nina Papadopoulos (BMC, 2024)
Abstract Background Functional somatic symptoms (FFS) and bodily distress disorders are highly prevalent across all medical settings. Services for these patients are dispersed across the health care system with minimal conceptual and operational integration, and patients do not currently access therapeutic offers in significant numbers due to a mismatch between their and professionals' understanding of the nature of the symptoms. New service models are urgently needed to address patients' needs and to align with advances in aetiological evidence and diagnostic classification systems to overcome the body-mind dichotomy. Method A panel of clinical experts from different clinical services involved in providing aspects of health care for patients with functional symptoms reviewed the current care provision. This review and the results from a focus group exploration of patients with lived experience of functional symptoms were explored by the multidisciplinary expert group, and the conclusions are summarised as recommendations for best practice. Results The mapping exercise and multidisciplinary expert consultation revealed five themes for service improvement and pathway development: time/access, communication, barrier-free care, choice and governance. Service users identified four meta-themes for best practice recommendations: focus on healthcare professional communication and listening skills as well as professional attributes and knowledge base to help patients being both believed and understood in order to accept their condition; systemic and care pathway issues such as stronger emphasis on primary care as the first point of contact for patients, resources to reduce the length of the patient journey from initial assessment to diagnosis and treatment. Conclusion We propose a novel, integrated care pathway for patients with 'functional somatic disorder', which delivers care according to and working with patients' explanatory beliefs. The therapeutic model should operate based upon an understanding of the embodied nature of patient's complaints and provide flexible access points to the care pathway.